2009
DOI: 10.1021/np800702c
|View full text |Cite
|
Sign up to set email alerts
|

Isariotins E and F, Spirocyclic and Bicyclic Hemiacetals from the Entomopathogenic Fungus Isaria tenuipes BCC 12625

Abstract: New spirocyclic and bicyclic hemiacetals, isariotins E (1) and F (2), together with TK-57-164A (3) were isolated from the entomopathogenic fungus Isaria tenuipes BCC 12625. The absolute configuration of 3 was addressed by application of the modified Mosher's method. Isariotin F (2) exhibited activity against the malaria parasite Plasmodium falciparum K1 with an IC(50) value of 5.1 microM and cytotoxic activities against cancer cell lines (KB, BC, and NCI-H187) and nonmalignant (Vero) cells with respective IC(5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 22 publications
(36 reference statements)
0
24
0
Order By: Relevance
“…6) isolated from entomophatic fungi-afflicting insects [164]. 6) isolated from entomophatic fungi-afflicting insects [164].…”
Section: Perspectivesmentioning
confidence: 99%
“…6) isolated from entomophatic fungi-afflicting insects [164]. 6) isolated from entomophatic fungi-afflicting insects [164].…”
Section: Perspectivesmentioning
confidence: 99%
“…Corallolide B (8) is a naturally occurring diterpene isolated from the Caribbean gorgonian octocoral Pseudopterogorgia bipinnata collected near Providencia Island, Colombia, and reported to inhibit the growth of Mtb by 95% at 128 μg/mL in in vitro anti-TB assays [40]. The new spirocyclic and bicyclic hemiacetal, isariotin F (9), was isolated from the entomopathogenic fungus Isaria tenuipes BCC 12625 and displayed anti-TB activity against Mtb H 37 Ra with an MIC value of 60.4 μM [41]. Erythrophloin C (10) and suberosol B (11), two constituents from the roots of Beilschmiedia erythrophloia, exhibited anti-TB activity against Mtb H 37 Rv, showing MIC values of 50 and 28.9 μg/mL, respectively [42].…”
Section: Newly Reported Anti-tb Natural Products From 2009 To Presentmentioning
confidence: 99%
“…Recently, there has been a great deal of research pertaining to the modification of PA-824 [71][72][73][74][75]. It is believed that the stereochemistry of these molecules is also important as in the case of OPC-67683 (41). Analogue 42 bearing a chiral center of S-configuration has an excellent MIC of 0.8 1.6 μg/mL for H 37 Rv and shows nearly 60-times greater potency than its Rconfiguration analogue 43 [72].…”
Section: Some Cases Showing the Importance Of Stereochemistry In Semimentioning
confidence: 99%
“…[1] In a search for bioactive secondary metabolites of entomopathic fungi-afflicting insects, Bunyapaiboonsri et al reported isolating two novel compounds, isariotin E (3) and F (2) along with the known bicycle TK-57-164A (1), a compound previously described as an agricultural bactericide. [2,3] Isariotin F (2) exhibited activity against the malaria parasite Plasmodium falciparum K1, three cancer cell lines (KB, BC, NCI-H187), and nonmalignant (Vero) cells (IC 50 = 5.1, 15.8, 2.4, 1.6, and 2.9 mm, respectively). Furthermore Bunyapaiboonsri et al speculated that isariotin E (3) might serve as the biosynthetic progenitor of 1 and 2 (Scheme 1).…”
mentioning
confidence: 99%
“…Benefiting from Bunyapaiboonsris insight, [2] we suspected that the [3.3.1]-bicyclic nonane core found in compound 1 might arise via the intermediacy of an enol formed by the diastereoselective conjugate addition of methoxide to compound 3 (Scheme 1). An observation of a similar epoxide directed conjugate addition reported by Ogita and co-workers for scyphostatin supported this notion.…”
mentioning
confidence: 99%